Constraints in posterior-stabilised TKA kinematics: a comparison of two generations of an implant. - Pandit, H; van Duren, B; Price, M; Tilley, S; Gill, H; Thomas, N; Murray, D (2013)
PURPOSE: This study tests the hypothesis that the design changes incorporated in the newer generation Triathlon posterior-stabilised TKA design result in kinematics that more closely reproduce the kinematics observed in healthy knees than those achieved by the older generation Scorpio posterior-stabilised TKA design. METHODS: Eleven patients with Triathlon posterior-stabilised TKA, twelve patients with Scorpio posterior-stabilised TKA, and 22 subjects with normal asymptomatic knees underwent fluoroscopic assessment of the knee during a step-up exercise and a weight-bearing deep knee bend. Two-dimensional and three-dimensional knee kinematics were assessed including the maximum flexion, the patella tendon angle (PTA), the patella flexion angle (PFA), the minimum distance between cam and post, and the tibio-femoral contact positions. RESULTS: The average maximum flexion achieved was 114° (SD 3°), 91° (SD 10°), and 143° (SD 14°) for the Triathlon, Scorpio, and Normal groups. The average cam/post mechanism engagement was at 63° (SD 24°) and 82° (SD 16°) for the Triathlon and Scorpio groups. The condylar contact points showed a paradoxical anterior slide for the Scorpio group which was not present in the Triathlon group. The PTA and PFA values of both implants showed significant differences from normal. CONCLUSION: Overall, the Triathlon implant design, as compared to Scorpio TKA, produced kinematics closer to that of normal knees as proposed by the hypothesis. However, despite being closer to normal, the kinematics exhibited by the Triathlon group were still different from normal. A comparison of kinematic performance, taking into account altered design parameters, will contribute to improved understanding and future design considerations.